De novo retrotransposon insertion into the FGFR1 gene in a boy with congenital hypogonadotropic hypogonadism: a case report - Sawano, Kentaro; Nagasaki, Keisuke; Suzuki, Erina; Ogiwara, Yasuko; Kageyama, Ikuko; Fukami, Maki; Kuroki, Yoko (Frontiers in Endocrinology, 2025)
Congenital hypogonadotropic hypogonadism (CHH) is a rare endocrine disorder characterized by gonadal dysfunction attributed to impaired gonadotropin secretion. CHH is associated with approximately 60 genes including FGFR1. Nevertheless, the nucleotide variants of these genes are only related to less than half of the cases. Herein, we report a case of CHH caused by a novel mechanism. A 6-year-old boy presented with hypomasculinized genitalia, hyposmia, and syndactyly. Endocrine examinations showed impaired gonadotropin secretion. Short-read next-generation sequencing (NGS) identified the absence of mutations in the major causative genes for CHH. However, it detected an accumulation of discordant and split reads in a genomic region within the FGFR1 gene. Array-based comparative genomic hybridization did not detect copy-number abnormalities. Targeted long-read NGS and Sanger sequencing identified a de novo 333-bp insertion in exon 9 of the FGFR1 gene. A similarity search revealed that the insertion was an Alu element. This insertion caused a frameshift and resulted in premature termination (p. His409fsTer31). Further, it had several hallmarks of retrotransposition such as target site duplication, an endonuclease cleavage site-like motif, and a poly-A tail. The study results broadened the genetic basis of CHH that considered retrotransposon insertions. Importantly, this case emphasizes the need for additional genomic analyses in patients with CHH who had negative results on short-read NGS and array-based comparative genomic hybridization.